Influence of nitrate-containing arugula juice on nitrate-reducing oral bacteria and periodontopathogens in smokers’ biofilm - Bachtiar, Boy M.; Rieuwpassa, Irene E.; Susilowati, Heni; Indrawati, Retno; Theodorea, Citra F.; Fath, Turmidzi; Bachtiar, Endang W. (Frontiers in Dental Medicine, 2025)
Green leafy vegetables such as arugula are rich in nitrates that support oral health, yet their effects on oral microbial balance, especially in smokers, remain unclear. This study evaluated the survival and activity of nitrate-reducing bacteria (NRB; Veillonella spp. and Rothia spp.) in biofilm exposed to nitrate-containing arugula juice (3.25 or 6.25 μM). The proportions of NRB were compared with periodontopathogens (Porphyromonas gingivalis and Fusobacterium nucleatum). Using quantitative real-time PCR (qPCR), we assessed bacterial survival and transcription of nitrate reductase genes (narG and napA) in biofilm from smokers and non-smokers. The results revealed that nitrate-containing arugula juice increased NRB bacteria abundance while reducing periodontopathogen growth. A higher level of nitrate (6.25 μM) increased nitrate reductase expression. Prolonged exposure (9 h) sustained the growth-promoting effect on Rothia spp. These results suggest that non-smokers have more nitrate-reducing bacteria in their biofilm, which promotes oral microbial balance. Thus, smokers might be advised to consume nitrate-containing arugula juice to promote NRB, which may have health benefits.